THE ANALYSIS OF INDONESIA ECONOMIC GROWTH: A STUDY IN SIX BIG ISLANDS IN INDONESIA - Teddy Christianto Leasiwal (Universitas Hayam Wuruk Perbanas, 2013)
This study attempts to investigate and analyze the factors determining and influencing the Indonesia'seconomic growth, and to see economic growth in the six bog islands in Indonesia, usingextension of the Solow-Swan model and endogenous growth models, by also adding the factors ofeducation (EDU), the potential sectors utilization (PSU) as well as several other factors that ForeignDirect Investment (FDI), Political Stability and Security (STAB). The results of this studyfound that the variable of FDI, PSU, EDU and STAB, in general, have effect on the economicgrowth in Indonesia and on the existing six big islands. Not all of these variables affect the 6 islandswhich is due to the different characteristics of each island. It can be concluded that theFDI, is still one of the important sources for Indonesia, and six big islands to encourage economicgrowth of Indonesia's economic growth and six big islands in Indonesia against the use ofpotential sectors especially in natural resources. Political Stability and Security (STAB), the conditionof Indonesia, and six big islands, are quite vulnerable to shocking security, making it havea strong effect on economic growth. Education (EDU) generally is able to contribute significantlyto the economic growth of the islands. In Bali and Timor, education (EDU) can not encourageeconomic growth.